ACCURACY OF THE TRANSLATION OF CULTURAL WORDS IN THE MAZE RUNNER NOVEL INTO INDONESIAN LANGUAGE - Widya Dara Anindya; Adi Sutrisno; Soepomo Poedjosoedarmo; Sigit Ricahyono (Universitas PGRI Madiun, 2020)
There have been plenty of studies on translation accuracy, but that focusing on cultural words under-investigated. The current study investigated the translation accuracy of The Maze Runner Novel in English by James Dashner into Indonesian by Yunita Candra. As many as 11 cultural words were collected. To measure the accuracy, questionnaires were distributed to 12 translators of at least 1 year of professional experience. The taxonomy developed by Pelawi (2014) covering categories of accurate (Ak), less accurate (KAk), and not accurate (TAk) was applied. Results show that (Ak) occurs 7/64%, (KAk) does 3/27%, and (TAk) does 1/9%. That a number of the data fall into the category of (KAk) and (TAk) indicate that while cultures share common features (universal), at the same time they contain characteristic features that are unique. It goes, therefore, no cultural expressions can be in total accuracy if they are transplanted into other cultures.